A new species and a new record of Sinella Brook (Collembola: Entomobryidae) from Guizhou Province, China - Wu, Jun; Huang, Cheng-Wang; Luan, Yun-Xia (Zootaxa, 2018)
Two species of Sinella Brook were discovered in an expedition to Maolan National Nature Reserve, Guizhou Province, China: S. maolanensis sp. nov. and S. colorata Zhang, Qu & Deharveng. The new species is characterized by the postlabial chaetae X, X2 and X4 ciliate and X3 smooth and the 6+6 central mac on the fourth abdominal segment. It differs from the closely related species by the combination of postlabial chaetae and abdominal chaetotaxy. Sinella colorata is a new record from the province. A key to the eyeless Sinella species from China is provided.